Representasi Budaya Batak Dalam Film “Ngeri-Ngeri Sedap” Karya Bene Dion Rajagukguk - Aurillia, Tasya; Supriadi , Supriadi (LPPM Stikosa-AWS, 2024)
Movies are not only entertainment for society, but they also often address and present social issues within society. Films convey social and cultural realities to the public in their daily lives. Sometimes, movies also contain criticisms related to social issues surrounding the community, indirectly enhancing the audience's understanding of events in society. One of the films that tackles social and cultural issues is